Adsorptive removal of phenol from aqueous solution with zeolitic imidazolate framework-67. (15th March 2016) - Pan, Yong; Li, Zhi; Zhang, Zhe; Tong, Xiong-Shi; Li, Hai; Jia, Chong-Zhi; Liu, Bei; Sun, Chang-Yu; Yang, Lan-Ying; Chen, Guang-Jin; Ma, De-Yun
Abstract: ZIF-67(zinc-methylimidazolate framework-67), one of the zeolitic imidazolate frameworks (ZIFs), was used for the removal of phenol from aqueous solutions via adsorption and shows high adsorption capacity for phenol. The thermodynamic and kinetic adsorption behavior of ZIF-67 for phenol in water with concentration ranging from 50 to 300 ppm were investigated in a batch reactor and a ZIF-67 packed column, respectively. The effects of pH, contact time, zeta potential of the adsorbent and temperature on the adsorption behavior were evaluated, and the results demonstrated that the adsorption is primarily brought about by a specific favorable interaction (electrostatic interaction) between phenol and ZIF-67 surface. The suitability of the Langmuir adsorption model to the equilibrium data was investigated for each phenol-adsorbent system, which the results showed that the equilibrium data for all the phenol-sorbent systems fitted the Langmuir model. Thermodynamic parameters such as Gibbs free energy are calculated from the experimental data at different temperatures. The adsorbent could be perfectly regenerated at 120 °C with little loss in the adsorption ability. Graphical abstract: ZIF-67 performs high adsorption capacity for phenol from aqueous solutions and excellent reusability with simple thermal regeneration treatment. Highlights: ZIF-67 shows high adsorption capacity for phenol even though positivity was not high. Solution pH have significant influence on the removal of phenol. The removal of phenol by ZIF-67 fits pseudo-second order kinetic reaction law. Used ZIF-67 can be recycled for the adsorption by simple thermal regeneration. The ZIF-67 packed column shows excellent reusability for phenol adsorption even has been used two times.